2007
DOI: 10.1037/0033-2909.133.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory specificity and emotional disorder.

Abstract: The authors review research showing that when recalling autobiographical events, many emotionally disturbed patients summarize categories of events rather than retrieving a single episode. The mechanisms underlying such overgeneral memory are examined, with a focus on M. A. Conway and C. W. Pleydell-Pearce's (2000) hierarchical search model of personal event retrieval. An elaboration of this model is proposed to account for overgeneral memory, focusing on how memory search can be affected by (a) capture and ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

116
1,988
14
58

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,417 publications
(2,176 citation statements)
references
References 184 publications
(368 reference statements)
116
1,988
14
58
Order By: Relevance
“…Current findings suggest that ambiguity resolution is distorted in the effortful generation of interpretations and the selection of a single interpretation as most likely applicable to an ambiguous situation (Wisco & Nolen-Hoeksema, 2010). Concerning memory processes, strong evidence exists that depression is marked by biases in explicit memory, with depressed individuals reporting overgeneral and more negative memories than specific and positive memories compared with nondepressed individuals (Matt, Vazquez, & Campbell, 1992;Williams et al, 2007). In contrast, the data from studies examining mood-congruent implicit memory biases in depression is less conclusive (Barry, Naus, & Rehm, 2004; P. C. Watkins, 2002).…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 83%
“…Current findings suggest that ambiguity resolution is distorted in the effortful generation of interpretations and the selection of a single interpretation as most likely applicable to an ambiguous situation (Wisco & Nolen-Hoeksema, 2010). Concerning memory processes, strong evidence exists that depression is marked by biases in explicit memory, with depressed individuals reporting overgeneral and more negative memories than specific and positive memories compared with nondepressed individuals (Matt, Vazquez, & Campbell, 1992;Williams et al, 2007). In contrast, the data from studies examining mood-congruent implicit memory biases in depression is less conclusive (Barry, Naus, & Rehm, 2004; P. C. Watkins, 2002).…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 83%
“…Empirically supported mechanisms proposed to maintain negative cognition in depression include a tendency to ruminate in response to distress (Nolen-Hoeksema, 1991), systematic memory bias (Williams et al, 2007) and difficulties in solving interpersonal problems (Marx, Williams, & Claridge, 1992). As mentioned earlier in this chapter, most of the cognitive processes associated with depression have not been systematically investigated in people with psychosis.…”
Section: Limitations and Indications For Future Researchmentioning
confidence: 99%
“…As mentioned earlier in this chapter, most of the cognitive processes associated with depression have not been systematically investigated in people with psychosis. It is very plausible that the same constellation of memory impairment, ruminative thinking style and problem solving difficulty that accompany depression (Williams et al, 2007) could make it very difficult for someone with delusions to engage with reality testing or even to effectively gather evidence to assess the validity of distressing beliefs. Given the promising results of trials targeting these features to treat depression, it would be of worth to find out whether the same processes can contribute to the persistence of positive symptoms, in which case treatment trials in psychosis would be indicated.…”
Section: Limitations and Indications For Future Researchmentioning
confidence: 99%
“…Emotionally arousing memories interfere with this process and so the SMS inhibits the arousal features of the incoming memory by truncating the search at the general event level. Evidence in support of this inhibitory mechanism has been provided in experimental studies (Phillipot, Schaeffer & Herbette, 2003), and the notion of a truncated search at the general event level has recently been recruited to account for the phenomenon of overgeneral memory (see Williams, Barnhofer, Crane, Hermans, Raes, Watkins & Dalgleish, 2007 for a review).…”
Section: Remembering Emotional Events Differentlymentioning
confidence: 93%
“…Event specificity is central to word-cue studies that require participants to describe a discrete event that can be pinpointed in time and space (Crovitz & Schiffman, 1974), and this method has been particularly useful in assessing whether amnesic patients can recall remote specific events (see Kopelman, 1992 for a review). The specific-general dimension is integral to AM questionnaires used for clinical examination (Borrini, Dall"ora, Della Sala, Marinelli & Spinnler, 1989;Kopelman, Wilson & Baddeley, 1989) and the distinction is used extensively to study the phenomenon of overgeneral memory, which is the observation that certain people suffering from affective disorders have difficulty in retrieving specific events (Williams, 1996;Williams, Barnhofer, Crane, Hermans, Raes, Watkins & Dalgleish, 2007;Williams & Broadbent, 1986;Williams & Dritschel, 1992). Often the distinction is applied post hoc to memories produced without constraints and it is a central feature of studies examining the characteristics of self-defining memories (Singer, Rexhaj, & Baddeley, 2007;Singer & Salovey, 1993).…”
Section: The Structural Distinctionmentioning
confidence: 99%